Preface - Azmy S. Ackleh; Linda J. S. Allen; Graciela Canziani; Shandelle M. Henson; Jia Li; Zhien Ma (Mathematical Biosciences and Engineering)
Thomas Guy Hallam began his career as a faculty member inthe Department of Mathematics at Florida State University, workingin the area of comparison theorems for ordinary differentialequations. While at Florida State he organized a mathematicalmodeling course and thus became interested in mathematical biology.He began to wonder how he, as a mathematician, might address themounting environmental problems. He took courses in oceanography andecology and delved deeply into the literature. During the summer of1974, he gave a full series of lectures on mathematical biology atthe University of São Carlos in São Paulo, Brazil. In 1976,he took a year's leave at the University of Georgia, Athens, in theDepartments of Mathematics, Zoology, and the Institute of Ecology,where he met Tom Gard and Ray Lassiter, with whom he has hadcareer-long interactions. In Athens, he became interested inecotoxicology and partial differential equation models ofphysiologically structured populations. For more information please click the “Full Text” above.